CGIAR initiatives on sustainable agricultural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
In its first major programme since the mid-70s, the Consultative Group on International Agricultural Research (CGIAR) is planning three new initiatives for increasing and sustaining agricultural development and food production in developing...